THE ORIGINS AND THE SIGNIFICANCE OF THE TORONTO TECHNICAL SCHOOL, 1891 – 1904 - Sharman, Kathleen Yolande (Journal of Technical Education and Training, 2011)
This paper is about the school that began technical secondary education in the Province of Ontario, Canada. It is an historical case study that seeks to understand why the Toronto Technical School (TTS) was established, how it functioned for 13 years, and why it was amalgamated with public secondary education in 1904. This case history analyzes the rationale and purposes behind this first school and considers the impact of provincial control. TTS played a role that directly influenced provincial legislation which resulted in the formal recognition, public funding, and eventually, the inclusion of technical education in the public school system. The TTS still exists today and serves as a reminder of the original vision of a school designed and created for technical education. The findings of this study prompt critical questioning of the need to< continue separate educational space in the absence of the kind of support needed to make it a challenging and worthwhile option for students.